Model Pengembangan Al-Islam dan Kemuhammadiyahan Berbasis Mentoring - Siregar, Rosmaimuna; Romelah, Romelah; Nurhakim, Moh. (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
Muhammadiyah and Aisyiah Higher Education is a major role of the Muhammadiyah organization in advancing education in Indonesia, including the Muhammadiyah University of South. Dikti Litbang is a council in the Muhammadiyah organizational structure tasked with and authorized to foster and develop Al-Islam Kemuhammadiyahan. The AIK development model can be developed by the AIKÂ at Muhammadiyah and Aisyiah Higher Education, but is still guided by the AIK curriculum of the PP Muhammadiyah Higher Education Council. Thus, this research aims to find a model for the development of Al-Islam and Muhammadiyah implemented by LP-AIK. The results of this research can be used as an alternative for Muhammadiyah and Aisyiah Higher Education in Indonesia in developing AIK. The type of research is descriptive, with a qualitative approach that seeks to describe mentoring activities at campus. The data collected came from interviews with the head of LP-AIK, divisions, mentors, co-mentors, and several students. Mentoring guidebooks and rules are a source of data to view mentoring planning. The registration process, grouping, scheduling and implementation of mentoring are part of what is observed to see how the mentoring is carried out. The data obtained was grouped and then analyzed and discussed based on mentoring theory, thus arriving at a finding and conclusion regarding the mentoring-based AIK development model implemented by LP AIK.